A defence of witchcraft belief : A sixteenth-century response to Reginald Scot's Discoverie of Witchcraft - Pudney, Eric (Book collections on Project MUSE., 2021)
This edition of a previously unpublished manuscript defence of witchcraft belief offers a unique insight into learned opinion on the subject in Elizabethan England. It includes a comprehensive analytical introduction and will appeal to scholars with an interest in witchcraft across disciplinary boundaries.